KLORMETİL KETONLARIN 2-HİDROKSİ-BENZALDEHİTLERLE ETKİLEŞTİRİLEREK BENZOFURAN HALKASI İÇEREN KETONLAR VE ONLARIN ÇEŞİTLİ TÜREVLERİNİN SENTEZİ - KIRILMIŞ, CUMHUR (Fırat Üniveristesi, 2006)
Bu çalışmada; 1-kloro-3-mezitilaseton ile salisilaldehit, 5-brom salisilaldehit, 3-metoksi-salisilaldehit ve 2-hidroksi benzonitril; farklı çözücü ve baz karışımları kullanılarak yapısında hembenzofuran hem de mezitilen grubu içeren sübstitüe yeni benzofuran-2-il ketonların sentezi gerçekleştirildi.Bu reaksiyonlarda baz olarak NaOH, K2CO3 ve NaH kullanıldı.2-Hidroksi benzonitril ile 1-kloro-3-mezitilasetonun reaksiyonundan oluşan 1-(3-Aminobenzofuran-2-il)-2-mezitiletanon, çeşitli açil halojenürler (Asetil klorür, propiyonil klorür, benzoil klorür vefenilasetil klorür) ile amitlerine dönüştürüldü.Bis-benzofuran-2-il ketonun iki farklı metod ile sentezlendi. 1.Metod; salisilaldehit ile 1-klorasetonun etkileşimi sonucu oluşan 2-asetilbenzofuran, bromlanarak 2-bromoasetilbenzofuran eldeedildi. Oluşan yeni haloketon, tekrar salisilaldehit ile NaH bazı yanında etkileştirilip Bis-benzofuranketona, 2. Metod ise; 2 mol salisilaldehit ile 1,3-diklorasetonla K2CO3 bazı yanında etkileştirilip tekbasamakta Bisbenzofuran ketona dönüştürüldü. Her iki yolda da verimlerin birbirine yakın olduğugözlendi.Benzofuran ketonlar ile semikarbazon, alkol ve ketoksim sentezlendi. Ketoksimler ise farklı alkilhalojenür ve açil halojenürler ile K2CO3 bazı yanında etkileştirilerek uygun ketoksim eter ve ketoksimesterleri sentezlendi.Sentezlenen bileşiklerin yapıları, FT-IR, 1H ve 13C-NMR spektroskopik yöntemleri ile aydınlatıldı.Bazı bileşiklerin X-ışınları difraksiyonu verileri tezde verilmiştir. Ürünlerin erime noktaları DSC ile tayinedildi. Hesapanan ve deneysel elementel analiz sonuçları yapıları ile uyum içerisindedir.Anahtar Kelimeler: Mezitilen, benzofuran, semikarbazon, oksim eter, oksim ester.

In this study, mesitylene and benzofuran rings containing new ketones were synthesized from thereaction of 1-chloro-3-mesitylacetone with salicylaldehyde, 5-bromo salicylaldehyde, 3-methoxysalicylaldehyde and 2-hydroxy benzonitrile in different appropriate solvents. In these reactions, severalbases, such as NaOH, K2CO3, and NaH were used as neutralizing agents.1-(3-Aminobenzofuran-2-yl)-2-mesitylethanone which was synthesized from 2-hydroxy-benzonitrile and 1-chloro-3-mesitylacetone, was converted its novel amides by using with different acylhalogens. These acyl halogenes are mainly acetyl chloride, propanoyl chloride, benzoyl chloride andphenylacetyl chloride.Bisbenzofuran-2-yl-ketone was synthesized with two different methods. In the first method, 2-acetylbenzofuran which was synthesized from salicyl aldehyde and 1-chloroacetone, brominated on themethyl group of compound so as to obtain 2-(bromoacetyl)benzofuran. This new haloketone was convertedinto bis(benzofuran-2-yl)methanone with salicyl aldehyde in the presence of NaH. In the second method;bis(benzofuran-2-yl)methanone was directly synthesized from the reaction of 1,3-dichloroacetone andsalicyl aldehyde in the presence of K2CO3 . Yields of the two method are more or mately less same andsatisfactory.Obtained benzofuran ketones were converted into their semicarbazone, alcohol and oximederivatives. Ketoksimes were used in the synthesis of new oxime ethers and esters with appropriate alkyland acyl halogens in absolute acetone solvent in the presence of K2CO3 as neutralizing agent.The structure of the compounds have been characterized by mainly FT-IR, 1H-13C-NMRspectroscopy techniques. X-ray diffraction pattern of some selected compounds were obtained and given inthe thesis. Melting points were obtained by using DSC technique. Elemental analyses results were alsofound to be in good agreement with the determined structures.Keywords: Mesitylene, benzofurans, semicarbazones. oximethers, oximesters.
Synthesis of benzofuran containing ketones and their derivatives from the reaction of chloromethylketones with 2-hydroxybenzaldehydes
Keywords: Kimya